Bullous pemphigoid: Its incidence, mortality and clinical outcome in New Zealand. (24th March 2022) - Chung, Jenny G; Ramji, Rajan; Coomarasamy, Christin; Jarrett, Paul; Rademaker, Marius; Patel, Denesh C
ABSTRACT: Background/objectives: Bullous pemphigoid (BP) is an uncommon autoimmune bullous disorder, with significant morbidity and mortality. Mortality may be as high as 23.5% in the first year after diagnosis. Clear epidemiologic data across Australasia are lacking. Methods: A retrospective, multi‐centred cohort study was designed to determine the incidence and mortality of bullous pemphigoid in New Zealand. Data from all histopathologically diagnosed patients with bullous pemphigoid between 2009 and 2015 from the Auckland region were obtained. Demographics, clinical characteristics and outcome 3 years from diagnosis (until 31 December 2018) were collected. Demographic data were compared against a denominator year‐matched New Zealand Census population. Results: One hundred sixty‐one patients had confirmed bullous pemphigoid, with an incidence rate of 3.03/100 000 person‐years [95% CI 2.58–3.54]; 70% were of European ethnicity; 12.4% were Pacific peoples; 11.2% were Asian; and 6.8% were Māori. 45.3% had associated cognitive impairment and/or stroke. In the 3‐year follow‐up, 25% had treatment complications mostly from prednisone therapy. The mortality rate was 40%, highest in the first year of diagnosis, with age at diagnosis a predictor. Conclusion: The incidence and mortality rates are comparable to the UK/Northern Europe. Knowledge of the epidemiology of bullous pemphigoid in New Zealand and within an international settling informs the provision of future care and treatments.